The influence of different pre-formed holes on the dynamic response of square plates under air-blast loading. (August 2017) - Li, Ying; Wu, Weiguo; Zhu, Haiqing; Wu, Zhen; Du, Zhipeng
Abstract: Studying the blast response of plates with pre-formed holes under blast loading serves as a significant method to decouple dynamic response of plates with pre-formed holes under combined blast and fragment loading. Based on material test system (MTS) and Split Hopkinson tension bar (SHTB), the mechanical properties of experimental steel under different strain rates were obtained. Then, the experiments on the responses of plates with square, diamond and circular holes under air-blast loading were carried out and the failure modes of plates with diamond holes were derived. Later, the deformation curves of target plate were obtained by laser reverse forming technique. Next, a constitutive model program considering strain rate, stress status and temperature effect was adopted to carry out numerical simulation calculation, which verified the accuracy of this numerical simulation. Finally, discussions were carried out on the damage level at places where cracks might form, the dynamic stress concentration coefficient and stress status change, and then the influence which pre-formed holes have on the failure mode was analyzed. The results of this study show that: (1) A fortran vectorized user-material subroutine (VUMAT) program considering strain rate, stress status and temperature effect can effectively predict the dynamic response of metallic materials; (2) the shape of pre-formed holes affects the damage level, dynamic stress concentration coefficient and stress status. Besides, failure occurs more easily in plates with diamond pre-formed holes; (3) pre-formed holes have an obvious influence on the failure modes of plates under different blast distance. Highlights: Experiments were developed to study the response of plates with three types of pre-formed holes under blast loading. Numerical simulation with a modified fracture criterion is in good agreement with experiments.